IMPLEMENTATION AUTHORITY OF THE CONSTITUTIONAL COURT IN THE INDONESIAN CONSTITUTIONAL LAW SYSTEM - Moh. Thohir; Didik Sukriono (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
This study delves into the historical evolution and significance of Indonesia's Constitutional Court, focusing on its speculated super authority and independent interpretation of the Constitution. Rooted in the global context of judicial review, the research traces the court's pivotal role back to discussions during the Draft Constitution at BPUPKI and its prominence in the 1945 reform era. With the primary goal of providing a comprehensive understanding of the Constitutional Court's journey, the study sheds light on its distinctive authority and pivotal role within Indonesia's legal and constitutional framework. The research explores the court's exclusive jurisdiction, making its decisions final and binding and limiting legal recourse for dissatisfied parties. By examining the court's historical development and legal foundations, the study elucidates the Constitutional Court's role as a guardian of the constitution. The research reveals that the court's significance stems from its establishment as a constitutional guardian during the 1945 reform era, gaining prominence with the Third Amendment to the 1945 Constitution. The court's exclusive jurisdiction solidifies its position as a final arbiter in constitutional matters, shaping the legal landscape and restricting avenues for legal redress. In conclusion, the Constitutional Court has evolved into a central player in constitutional interpretation, wielding exclusive jurisdiction and serving as a final arbiter, emphasizing its unique authority and indispensable role in shaping Indonesia's legal and constitutional framework.